2013
DOI: 10.1007/s10126-013-9521-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Probiotic Phaeobacter Bacteria Grown in Biofilters Against Vibrio anguillarum Infections in the Rearing of Turbot (Psetta maxima) Larvae

Abstract: The rearing environment of first-feeding turbot larvae, usually with high larvae densities and organic matter concentrations, may promote the growth of opportunistic pathogenic Vibrionaceae bacteria, compromising the survival of the larvae. The aim of this study was to assess the effectiveness of the biofilm-forming probiotic Phaeobacter 27-4 strain grown on a ceramic biofilter (probiofilter) in preventing Vibrio anguillarum infections in turbot larvae. In seawater with added microalgae and maintained under tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…To circumvent the need for prophylactic use of antibiotics in aquaculture, the application of probiotics seems to hold great potential and previous studies have demonstrated a clear probiotic effect of the Roseobacter clade bacterium Phaeobacter inhibens in axenic model systems (D'Alvise et al, 2012(D'Alvise et al, , 2013Grotkjaer et al, 2016;Prol-García and Pintado, 2013). Our results demonstrate that moving P. inhibens from an axenic model system to a defined non-axenic, and ultimately to a completely non-axenic, live feed model system, does not interfere with the establishment of the potential probiont, nor with its antagonistic effects on the fish pathogenic bacterium Vibrio anguillarum.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent the need for prophylactic use of antibiotics in aquaculture, the application of probiotics seems to hold great potential and previous studies have demonstrated a clear probiotic effect of the Roseobacter clade bacterium Phaeobacter inhibens in axenic model systems (D'Alvise et al, 2012(D'Alvise et al, , 2013Grotkjaer et al, 2016;Prol-García and Pintado, 2013). Our results demonstrate that moving P. inhibens from an axenic model system to a defined non-axenic, and ultimately to a completely non-axenic, live feed model system, does not interfere with the establishment of the potential probiont, nor with its antagonistic effects on the fish pathogenic bacterium Vibrio anguillarum.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics play an important role in welfare of host by maintaining a healthier balance of intestinal microflora which not only provides a defensive barrier against colonization of harmful bacteria but also stimulates host immune system (Gomez & Balcazar ; Cain & Swan ; Gaggia, Mattarelli & Biavati ). Probiotics when used as water additive may act like a biological control agent and manipulate the microbial population of the environment by reducing or eliminating pathogenic micro‐organisms which is often realized as increase in animal survival (Luis‐Villasenor, Macias‐Rodriguez, Gomez‐Gil, Ascencio‐Valle & Campa‐Cordova ; de Souza, Suita, Leite, Romano, Wasielesky & Ballester ; Prol‐Garcia & Pintado ; Silva, Soares, Calazans, Vogeley, do Valle, Soares & Peixoto ; Zokaeifar et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoalteromonas, Roseobacter, and Vibrionaceae bacteria have been suggested as probiotics in aquaculture (7)(8)(9). However, our results suggest that several Pseudoalteromonas and Vibrionaceae strains may not be suitable, since they can be toxic to Artemia sp.…”
Section: Discussionmentioning
confidence: 68%
“…These species predominantly belonged to the Actinobacteria class, the Pseudoalteromonas genus, Roseobacter clade, and the Photobacteriaceae and Vibrionaceae families (3,5,6). Due to their antagonistic activity, live cultures of bacteria from Pseudoalteromonas, Phaeobacter, Ruegeria, and Vibrio genera are not only of interest as sources of novel pharmaceuticals but also as probiotics in fish and shellfish aquaculture systems (7)(8)(9).…”
mentioning
confidence: 99%